Antegrade continence enema stoppers: a pilot study on patient preferences. (11th August 2022) - Hooker, Emily; Martin, Benjamin; Gee, Oliver; Jester, Ingo
Abstract : Background: Severe constipation can have a major impact on a child's quality of life and that of their families. Forming an antegrade continence enema (ACE) can be a transformational intervention to manage severe symptoms. However, operations can also have unpredictable negative consequences such as stomal stenosis or leaks from the ACE site. Aim: To investigate whether the choice of an ACE stopper can increase patient satisfaction and compliance. Methods: A service evaluation with a standardised questionnaire was completed to assess quality of life and explore factors that have an impact on the preference for which ACE stopper was used. Results: In total, 17 patients completed the evaluation of all three ACE stopper devices. At least 75% of the children improved their stooling pattern with an overall satisfaction rate of 8.5 out of 10. More patients preferred a flexible stopper but no one device was strongly preferred over the others. Conclusion: The study shows that an ACE has a positive impact on quality of life. With regards to the choice of ACE stopper, results show that different stoppers suit different individuals, highlighting that there is a place for a choice. This is useful information for healthcare providers who wish to improve compliance and reduce the risk of complications in this patient group.